PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN KETERAMPILAN PRODUKTIF TERHADAP KARAKTER KEWIRAUSAHAAN PADA SISWA KELAS XI TKRO SMKN 2 TULUNGAGUNG - Reka Yuliana; Sri Wulan Yanuari (Oikos : Jurnal Ekonomi dan Pendidikan Ekonomi, 2021)
This study aims to determine the effect of learning entrepreneurship and productive skills on entrepreneurial character in the tenth grade students of Smkn 2 Tulungagung. This research is categorized as a quantitative descriptive study with a population of 102 students who are students of class XI tkro Smkn 2 Tulungagung. Data collection was carried out using questionnaire and questionnaire techniques. Data collection methods using questionnaire questionnaire, the instrument used in the form of questions with answers that have been available answers consisting of 5 (five) options with scoring = answer a score 5, answer b score 4, answer c score 3, answer d score 2, answer e score 1. The sum of each variable 8 and 9 questions so that the lowest value is 8 and the highest value is 45. To find out the relationship between the two variables X and Y use the Likert scale formula. From the results of multiple linear regression tests can be seen from the table "coefficients", obtained equation Y = 10.830 + 0.305X1 + 0.492X2 where (a) is a constant of 10.830 states that if the independent variable (entrepreneurial learning and productive skills) is 0 (zero) then the value of the dependent variable (entrepreneurial character) of 10,830, (b1) is a regression coefficient of X1 regression coefficient 0.305 states that each addition of one unit of variable X1 assuming other variables X2 is constant then this will affect the increase in the magnitude of y by 0.305 and (b2) a regression coefficient of X2 0.492 regression coefficient states that each addition of one unit of variable X2 assuming another variable (X1) is constant then this will affect the increase in the amount of Y by 0.492. Because it can be given to students of class XI SMK Negeri 2 Tulungagung.